Gaya Komunikasi Pemimpin Perempuan di Lingkungan Sekretariat Daerah Kabupaten Magelang - Chasanah, Novi Nikmatul Nur; Wismaningtyas, Tri Asih; Christiana, Lintang Citra (Journal of Public Administration and Local Governance, 2023)
Gender equality is still a problem because of negative perceptions for women. Women are considered weak and unable to lead an organization. This gives rise to the glass ceiling phenomenon, namely that it is considered difficult for women to advance to positions. Magelang Regency has several female leaders in Regional Apparatus Organizations (OPD) who are competent and accomplished. The aim of this research is to determine the communication style of female leaders in Magelang Regency. This research uses a descriptive qualitative approach with data collection methods in the form of interviews, observation and literature study. The results of this research show that female leaders in the Magelang Regency OPD have various leadership communication styles. Women's leadership communication styles have their own characteristics and are based on each individual and cannot be generalized like stereotypes in society. Of the three Heads of OPD in Magelang Regency, it can be analyzed that Mrs. Siti Zumaroh (Head of BPPKAD) is included in the Iron Maden theory (firm), Mrs. Umi Haniyati Chauliyanah (Inspector of the Inspectorate) is included in the Middle-Of-The-Road Style category (middle ) and Mrs. Bela Pinarsi (Head of PPPA Social Services) are included in the Mother category.